A constituição do ethos feminino nas histórias em quadrinhos de Maurício de Sousa - Silva, Andreia Cristina da (2008)
This dissertation is in the Rhetoric and New Rhetoric fields and aims to analyze how the female ethos is formed rhetorically in the Maurício de Sousa’s HQs. The HQs constitute one of the most popular reading instruments, above all among children and teenagers. We have the hypothesis that in the presence of this very big public that they have, the HQs own power to circulate social and behavior papers. The corpus is formed by eight complete histories and some stretches that are significant to our studies. They permit us to verify how the woman even meets herself in the clash between old and new discourses. The mainly question of this research inquires how nowadays the female’s ethos in the HQs constitute and if the woman is really free of the traditional model established by the dominant discourse that held out by centuries. The results show that the woman, spite of desire to live a new model, where she can be free and independent, she even has big difficulties to free of traditional models. The called “modern woman” do not constitute really in a new woman, but she lives between two distinct discourses that incite strong conflicts and leave her without know exactly what is her real paper.